Hepatitis B and the seroconversion status of oral health assistants in Primary Care - An association of immunological profile and influencing factors (Research, Society and Development, 2021)
Scale sociodemographic characteristics, knowledge about Hepatitis B, self-care practices in health, as well as the association of these variables with the immunological profile of oral health assistants through anti-HBsAg enzymatic assays and immunochromatography. This is a cross-sectional epidemiological study carried out in Primary Care in 40 municipalities in the northwest region of the State of São Paulo, served by the DRS II. Data collection was structured in stages, in the first stage, self-administered semi-structured questionnaires were used, dimensioned in demographic domains, knowledge and self-care practices in health. The second consisted of analyzing the participants' immunization records, followed by checking the immunization status of the ASBs using a rapid anti-HBsAG immunochromatographic assay. Data analysis was performed using the Statistical Package for the Social Sciences software, using Pearson's chi-square test, Fisher's exact test, maximum likelihood ratio test and the Kolmogorov-Smirnov normality test (p